2008
DOI: 10.1371/journal.pone.0003604
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule, Non-Peptide p75NTR Ligands Inhibit Aβ-Induced Neurodegeneration and Synaptic Impairment

Abstract: The p75 neurotrophin receptor (p75NTR) is expressed by neurons particularly vulnerable in Alzheimer's disease (AD). We tested the hypothesis that non-peptide, small molecule p75NTR ligands found to promote survival signaling might prevent Aβ-induced degeneration and synaptic dysfunction. These ligands inhibited Aβ-induced neuritic dystrophy, death of cultured neurons and Aβ-induced death of pyramidal neurons in hippocampal slice cultures. Moreover, ligands inhibited Aβ-induced activation of molecules involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(171 citation statements)
references
References 50 publications
9
162
0
Order By: Relevance
“…After 24 months of ex vivo NGF gene delivery, no long-term adverse effects are found and a marked reduction of the rate of cognitive decline and an increase of cortical glucose metabolic uptake are detected in treated subjects (Tuszynski et al, 2005). Finally, Longo et al (2007) are testing small molecule p75(NTR) ligands with the unique ability to block Ab-induced activation of molecules involved in AD pathology (i.e., calpain/cdk5, GSK3b and c-Jun, and tau phosphorylation) to prevent Ab-dependent AKT and CREB inactivation, to reverse synaptic impairment and to inhibit Ab-induced neuronal dystrophy and death (Yang et al, 2008).…”
Section: Ngf and Its Receptors In Admentioning
confidence: 99%
“…After 24 months of ex vivo NGF gene delivery, no long-term adverse effects are found and a marked reduction of the rate of cognitive decline and an increase of cortical glucose metabolic uptake are detected in treated subjects (Tuszynski et al, 2005). Finally, Longo et al (2007) are testing small molecule p75(NTR) ligands with the unique ability to block Ab-induced activation of molecules involved in AD pathology (i.e., calpain/cdk5, GSK3b and c-Jun, and tau phosphorylation) to prevent Ab-dependent AKT and CREB inactivation, to reverse synaptic impairment and to inhibit Ab-induced neuronal dystrophy and death (Yang et al, 2008).…”
Section: Ngf and Its Receptors In Admentioning
confidence: 99%
“…It was found to selectively inhibit binding of NGF and proNGF to p75 NTR at higher concentrations, and in the low nanomolar range induced p75 NTR -dependent NFjB and AKT activations, which were required for the compound's prosurvival effects [32]. The compound was subsequently reported to inhibit Ab-induced cell death in hippocampal, cortical, and septal neurons, decrease activity in a range of toxic/apoptotic signaling pathways, and reverse Ab-mediated neuritic dystrophy and impairment of hippocampal long-term potentiation [33]. Furthermore, LM11A-31 has been shown to inhibit chemotherapeutic agentinduced rhoA signaling [34], and has shown excellent oral absorption, blood-brain barrier penetration and tolerability, and mitigates pathology in models of spinal cord injury and Alzheimer's disease [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Both NGF and the mimetics were able to inhibit the ability of A to down regulate Akt signaling; in contrast, the peptidomimetics demonstrated p75-dependent inhibition of A-induced GSK3b and A-induced JNK activation, whereas NGF could not affect these latter two activities. Thus, these loop 1 peptidomimetics induced additional survival promoting cell signaling via p75 in presence of A, not observed with NGF via p75 (Yang et al, 2008). Hence, the selectivity progressed from receptor to signaling pathway.…”
Section: Small Molecule P75 Agonists and Antagonistsmentioning
confidence: 86%
“…The survival response observed was mediated by NF-κB and the PI3K-Akt pathway (Massa et al, 2006). They further demonstrated that the mimetics were able to rescue the neurons from proNGF-induced (Massa et al, 2006) or A-induced (Yang et al, 2008) cell death, which have implications for Alzheimer's pathogenesis. NGF, even though it can bind p75, was not able to prevent the A-induced neuritic dystrophy.…”
Section: Small Molecule P75 Agonists and Antagonistsmentioning
confidence: 91%
See 1 more Smart Citation